Blunt trauma head injuries and time to death in the cases autopsied at a tertiary care centre - Sah, Bikash; Yadav, B N; Jha, S (Journal of BP Koirala Institute of Health Sciences, 2018)
Background: In developing countries, accident rates in general and traumatic head injuries in particular are increasing as traffic increases besides other factors like industrialization, falls and ballistic trauma. Most injury related deaths and disabilities are preventable. Objective: To find out the relationship between the extent and severity of fatal blunt trauma injuries in head region with duration of survival (time to death), place of death, hospitalization status and intoxication status. Methods: This was a hospital based, cross sectional and analytical study done on the cases brought for postmortem examination at a mortuary of B. P. Koirala Institute of Health Sciences, Dharan, Nepal over one year period (13th April 2012 to 13th April 2013). Appropriate statistical test was used to compare the Injury Severity Score (ISS) with duration of survival, place of death, hospitalization status and intoxication status. Result: Significant difference was present between ISS of hospitalized cases and not hospitalized cases, of cases who died within half an hour (spot death) and between half hour and 6 hour (death at emergency) but there was no significant difference among other different cases who were hospitalized and between intoxicated and not intoxicated at the incident. Conclusion: This study has shown the time to death in blunt trauma head injury cases with higher ISS is less as compared to those with less ISS. The ISS is also significantly different for hospitalized and not hospitalized cases. This shows us to focus more on preventive strategies of such injuries. Journal of BP Koirala Institute of Health Sciences, Vol. 1, No. 1, 2018, page:7-13